Nothing lost a novel - Dunne, John Gregory 1932-2003 (Knopf, 2004)
The brutal killing of black drifter Edgar Parlance ignites a destructive circus of the media, power politics, legal infighting, passion, and more for a rural midwestern town and the diverse characters involved.
Keywords: African American men -- Crimes against -- Fiction; Mystery fiction